2014
DOI: 10.1159/000362450
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Longitudinal Study of Thyroid Function in Children with Down's Syndrome

Abstract: Background/Aims: The natural history of thyroid function in children with Down's syndrome is relatively unknown. We hypothesized that in these patients the occurrence of thyroid dysfunction rises during development. Methods: Thyroid function was assessed yearly in 145 children with Down's syndrome, all followed from birth up to 10 years of age. Heteroskedastic binary and ordinary logistic regression for repeated measures was used to evaluate the relationship of thyroid function with continuous time. Results: C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
29
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 41 publications
4
29
0
3
Order By: Relevance
“…During a 10‐year longitudinal study of thyroid function in children with DS, over half of the children developed some type of thyroid dysfunction (Iughetti et al, ), lending strong evidence in support of a recommended maximum post‐infancy screening interval of 1 year. Following routine screening protocols established in our clinic, analysis of our cohort revealed a total of 23.1% meeting diagnostic criteria for hypothyroidism, including 5% diagnosed congenitally, 10.9% with acquired hypothyroidism and the remaining 7.2% having subclinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…During a 10‐year longitudinal study of thyroid function in children with DS, over half of the children developed some type of thyroid dysfunction (Iughetti et al, ), lending strong evidence in support of a recommended maximum post‐infancy screening interval of 1 year. Following routine screening protocols established in our clinic, analysis of our cohort revealed a total of 23.1% meeting diagnostic criteria for hypothyroidism, including 5% diagnosed congenitally, 10.9% with acquired hypothyroidism and the remaining 7.2% having subclinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Another key area of interest is in the management of immunerelated disorders. On one hand, people with DS show increased incidence of autoimmune disorders such as autoimmune hypothyroidism 51 , celiac disease 7 , and myriad autoimmune skin conditions 52 , indicating a hyperactive immune system. Conversely, people with DS show increased risk to specific bacterial infections, with bacterial pneumonia being a leading cause of death 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid dysfunction is the most common endocrine abnormality in patients with DS (Hawli et al, ; Iughetti et al, ), but prevalence estimates vary widely, ranging between 3% and 54% in adults (Hawli et al, ). The established risk factors for thyroid dysfunction in DS include old age and female sex (Rose and Brown, ).…”
Section: Clinical Features Of Dsmentioning
confidence: 99%
“…Evidence indicates that the frequency of hypothyroidism in neonates with DS is 28 times higher than expected in the general population (Purdy et al, ). Recently, a 10‐year longitudinal study demonstrated that the probability of acquired thyroid dysfunction in DS increased from 30% at birth to 49% at 10 years of age (Iughetti et al, ). Several mechanisms have been proposed to explain the increased incidence of hypothyroidism in DS, including immaturity of the hypothalamic‐pituitary‐thyroid axis (Sharav et al, ), inappropriate thyroid stimulating hormone (TSH) secretion (Gruñeiro de Papendieck et al ), TSH insensitivity (Gibson et al, ), and reduced TSH bioactivity (Gibson et al, ).…”
Section: Clinical Features Of Dsmentioning
confidence: 99%